IMPLEMENTASI PENILAIAN OTENTIK DALAM MATA PELAJARAN BAHASA INDONESIA DI SMA NEGERI 1 PAINAN - Wahyuni, Rama Kurnia; Atmazaki, Atmazaki (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this research are three (1) types of authentic assessment used by teachers in Indonesian language subjects in SMA Negeri 1 Painan, (2) conformity assessment between teacher done authentic language subjects Indonesia in SMA Negeri 1 Painan and theory on the curriculum of 2013, and (3) the obstacles faced by Indonesian language teachers in SMA Negeri 1 Painan. This research type is qualitative research using descriptive method. Data collection techniques were conducted by observation, interview, and documentation study. Based on research findings and research results can be concluded the following three things. (1) Overall type of authentic assessment has been used by Indonesian teachers in SMA Negeri 1 Painan. (2) Overall the appropriateness between authentic assessment of Indonesian language teachers in SMA Negeri 1 Painan and the theory that existed in the Curriculum 2013 is good. Pthere is a component of the understanding of the process and the assessment of learning based on data obtained in the study is categorized well. Indonesian language teacher SMA Negeri 1 Painan already understand the process and assessment of learning well. In the component of the implementation of the assessment of learning based on the data obtained in the study categorized quite well. Indonesian language teacher SMA Negeri 1 Painan has conducted a fairly good learning appraisal. Kata kunci: Implementasi Penilaian Otentik, Bahasa Indonesia